Primary geography - Scoffham, Stephen; Bridge, Colin (HarperCollins Publishers, 2014)
Description: Collins Primary Geography has been developed to provide full coverage of the national curriculum requirements for geography in the primary school. The four Key stage 2 primary geography books provide a progressive, skills based scheme for the junior years. Each book is divided into units covering physical, human and environmental geography. There are also case studies of contrasting localities in the UK, Europe, Asia and the wider world. The pupil books use an extensive range of evidence to stimulate the children’s interest and encourage investigative skills - photographs, maps, satellite images artwork, charts and diagrams. Each pupil book has an accompanying teacher’s guide which contains copymasters. Locations focussed on in Book 3 include: Scotland, France, Canada, India.